Digital Marketing: Implementation in Marketing MSME Crush Chips Products in Palembang - Muhammad Furqon (Universitas Bangka Belitung, 2024)
The purpose of the study is to investigate the difficulties and digital marketing tactics employed by UMKM Crush Chips in Palembang. The research object is Crush Chips, a MSMEs that makes chips in Palembang, and the research method is qualitative descriptive with purposive sample approaches. The information was gathered by watching and interviewing the proprietors of Crush Chips businesses. According to research, Crush Chips' marketing efforts make use of social media platforms including Facebook, Instagram, Whatsapp, and TikTok, in addition to alliances with online retailers like Shopee Foods, Grab-Food, and Go-Food. By using innovative and engaging content, they were able to increase sales and customer contact. Still, Crush Chips has to deal with a number of issues, including inadequate capital, a shortage of SDMs who meet the requirements, and inadequate internet and infrastructure connectivity. Their capacity to create more potent digital marketing tactics is hampered by these difficulties. Therefore, it can be said that while MSMEs Crush Chips has shown tenacity and inventiveness in utilizing digital marketing tactics, there are still issues that need to be resolved, such as a shortage of financing and the constraints of SDM and infrastructure. In order for Crush Chips to maintain sustainable growth and competitiveness in the digital market, efforts must be made to overcome these obstacles.